Women’s Informal Employment And Fertility Rate: A Concern On Population Growth - Abdul Malek, Nazurah; Idris, Zera Zuryana (2016)
Population growth is a vital component of sustainable development as it ensures the continuity of human capital formation process. There is limited prior research that specifically examines the relationship between women participation in informal activities and the concept of sustainable development. Using the Ordinary Least Square regression method, this paper attempts to study the impact of women participation in informal employment on population growth. Taking the most present statistical update for 47 countries from different regions provided by the International Labour Organisation (ILO), this study found that women involvement in the informal economy does affect fertility rate positively. This provides some support that the nature of women’s employment or the kinds of jobs and working conditions provide alternative returns and satisfactions to having children. The result of this study may assist in the formation of the labour policy process to enjoy a sustainable economic growth.